Implementation Of State Owned Goods Management Policy In Makassar City port Authority Office - Muhammad Rizky Rachmadi (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study aims to describe the Implementation of State Property Management Policy at the Main Port Authority Office of Makassar City. And analyze it by adjusting it to the theories that are in the implementation model literature of George C. Edward III. The results of this study used indicators of success according to the theory of George C. Edward III, namely: (1) Communication (2) Resources (3) Disposition or Attitude of Executors (4) Bureaucratic Structure. The researcher chose to refer to the Policy Implementation theory, because according to the researcher this theory was relevant to the problems the writer encountered while in the field and was easy to understand and more appropriate for measuring the success of an implementation in the management of State Property at the Makassar Main Port Authority Office. Because this theory has four indicators that are related to each other, so if one of these components fails, the policy implementation cannot run optimally. Because the practical implementation of the policy requires the existence of several related components so as to make it directed. Data collection techniques with interviews, observation, and documentation. This research is a descriptive qualitative research.